Konsep Sebayatn Suku Dayak Barai Sebagai Tempat Setelah Kematian Dalam Perspektif ‘Hidup Kekal’ Ensiklik Spe Salvi - Siong (Perspektif, 2022)
This article focuses on The Concept of Sebayatn of Dayak Barai Tribe as a Place After Death in the Perspective of ‘Eternal Life’ of Encyclical Spe Salvi. One of the problems being faced by local churches in West Kalimantan, particularly in the area where the Dayak Barai domicile, namely Kayan downstream, is the tension between Christian teachings and local wisdom values. These two perspectives are often misunderstood by the local community, even the Dayak Barai tribe itself considers the presence of the Catholic Church to threaten existing local Wisdom values. Sebayatn is one of the sensitive concepts discussed among the Dayak Barai tribe, apart from being taboo to talk about, this concept when confronted with the Christian concept of salvation can lead to theological contradictions and beliefs. Therefore, this research was conducted within the framework to ignite a religious discussion between the culture of the Dayak Barai tribe and Christian theology. The finding is that the concept of the place of the dead of the Barai people is not much different from the concept of the world of the dead in Christianity. Keywords: Dayak Barai, Culture, Sebayatn, Eternal Life, Theology. Abstrak Artikel ini berfokus pada Konsep Suku Dayak Barai Sebayatn sebagai Tempat Setelah Kematian dalam Perspektif Ensiklik ‘Hidup Kekal’ Spe Salvi. Salah satu masalah yang dihadapi oleh gereja-gereja lokal di Kalimantan Barat, khususnya di daerah domisili Dayak Barai, yaitu Kayan di hilir, adalah ketegangan antara ajaran Kristen dan nilai-nilai kearifan lokal. Kedua perspektif ini seringkali disalahartikan oleh masyarakat setempat, bahkan suku Dayak Barai sendiri menganggap kehadiran Gereja Katolik mengancam nilai-nilai kearifan lokal yang ada. Sebayatn merupakan salah satu konsep sensitif yang diperbincangkan di kalangan suku Dayak Barai, selain tabu untuk dibicarakan, konsep ini jika dikonfrontasikan dengan konsep keselamatan Kristen dapat menimbulkan kontradiksi teologis dan kepercayaan. Oleh karena itu, penelitian ini dilakukan dalam rangka menyulut diskusi keagamaan antara budaya suku Dayak Barai dengan teologi Kristen. Temuannya, konsep tempat orang mati orang Barai tidak jauh berbeda dengankonsep dunia orang mati dalam agama Kristen.